The low-temperature heat capacity of fullerite C₆₀ - Bagatskii, M.I.; Sumarokov, V.V.; Barabashko, M.S.; Dolbin, A.V.; Sundqvist, B. (Физика низких температур, 2015)
The heat capacity at constant pressure of fullerite C₆₀ has been investigated using an adiabatic calorimeter in
a temperature range from 1.2 to 120 K. Our results and literature data have been analyzed in a temperature interval
from 0.2 to 300 K. The contributions of the intramolecular and lattice vibrations into the heat capacity of C₆₀
have been separated. The contribution of the intramolecular vibration becomes significant above 50 K. Below
2.3 K the experimental temperature dependence of the heat capacity of C60 is described by the linear and cubic
terms. The limiting Debye temperature at T → 0 K has been estimated (Θ0 = 84.4 K). In the interval from 1.2 to
30 K the experimental curve of the heat capacity of C₆₀ describes the contributions of rotational tunnel levels,
translational vibrations (in the Debye model with Θ0 = 84.4 K), and librations (in the Einstein model with
ΘE,lib = 32.5 K). It is shown that the experimental temperature dependences of heat capacity and thermal expansion
are proportional in the region from 5 to 60 K. The contribution of the cooperative processes of orientational
disordering becomes appreciable above 180 K. In the high-temperature phase the lattice heat capacity at constant
volume is close to 4.5 R, which corresponds to the high-temperature limit of translational vibrations (3 R) and
the near-free rotational motion of C60 molecules (1.5 R).